2015
DOI: 10.1021/acs.est.5b00506
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure and Soil pH Determine Chemoautotrophic Carbon Dioxide Fixation in Drained Paddy Soils

Abstract: Previous studies suggested that microbial photosynthesis plays a potential role in paddy fields, but little is known about chemoautotrophic carbon fixers in drained paddy soils. We conducted a microcosm study using soil samples from five paddy fields to determine the environmental factors and quantify key functional microbial taxa involved in chemoautotrophic carbon fixation. We used stable isotope probing in combination with phospholipid fatty acid (PLFA) and molecular approaches. The amount of microbial (13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 38 publications
3
21
2
Order By: Relevance
“…However, we observed that there was no significant correlation between AP and the top 50 bacterial genera. In a previous study, bacterial abundance was positively associated with soil pH [19], and pH differences were the main factor influencing soil archaeal diversity and community structure in the tropical zone and chemoautotrophic carbon dioxide fixation in drained paddy soils [62, 63]. Environmental factors clearly affected the bacterial community in this study and were the main reason for their differences in abundance.…”
Section: Discussionsupporting
confidence: 48%
“…However, we observed that there was no significant correlation between AP and the top 50 bacterial genera. In a previous study, bacterial abundance was positively associated with soil pH [19], and pH differences were the main factor influencing soil archaeal diversity and community structure in the tropical zone and chemoautotrophic carbon dioxide fixation in drained paddy soils [62, 63]. Environmental factors clearly affected the bacterial community in this study and were the main reason for their differences in abundance.…”
Section: Discussionsupporting
confidence: 48%
“…These results are similar to the ones found in our study. Soil TOC and cbbl abundance exhibited a significant positive correlation, in line with the view that soil organic carbon and pH are the most significant factors influencing the community composition, abundance, and activity of the cbbl bacteria(Yuan et al 2012;Long et al 2015). The value of soil pH was also significantly correlated with the abundance of AOB and nifH.…”
supporting
confidence: 81%
“…Table 4). They were the most significant factors influencing the community composition, abundance, and activity of the cbbl bacteria [51][52]. The above results show that different nitrogen fertilization rates can change the soil nutrient content, and changes of soil nutrients could promote the abundance of nutrient cycling microbial changed, and different soil nutrients can affect different functional microbes.…”
Section: Relative Abundance Of Functional Microbialmentioning
confidence: 81%